My name is Jody Williams : a Vermont girl's winding path to the Nobel Peace Prize - Williams, Jody, 1950- (California series in public anthropology, 2013)
As Eve Ensler says in her inspired foreword to this book, "Jody Williams is many things-a simple girl from Vermont, a sister of a disabled brother, a loving wife, an intense character full of fury and mischief, a great strategist, an excellent organizer, a brave and relentless advocate, and a Nobel Peace Prize winner. But to me Jody Williams is, first and foremost, an activist."From her modest beginnings to becoming the tenth woman-and third American woman-to receive the Nobel Peace Prize, Jody Williams takes the reader through the ups and downs of her tumultuous and remarkable life. In a voic.